Effect of accelerated ageing on germination and vigour in pigeonpea (Cajanus cajan) - K. KANAKA DURGA,; K. KESHAVULU,; M. JYOTHI,; R. ANKAIAH,; M. GANESH, (Seed Research, 2026)
The study was conducted at SRTC, Rajendranagar, during 2007 to find out the effect of accelerated ageing (AAT) on germination and vigour in pigeonpea (Cajanus cajan L.). The germination was high in fresh seed lots compared to carry-over seed lots in all the genotypes (Asha, Palnadu and Laxmi) at different intervals after AAT. Gradual decrease in accelerated ageing was noticed with increase in period of accelerated ageing. Similar trend was noticed with respect to seedling vigour index on length and dry-weight basis. Seedling vigour index on length and dry-weight basis was found to be more in Asha, followed by Laxmi using both the methods of evaluation. The electrical conductivity of seed leachates gradually increased with the period of accelerated ageing and was high in carry-over seed lots compared to fresh seed lots in all the genotypes. The increase in EC was more for Palnadu (252.26%), followed by Laxmi (180.39%) and Asha (110.98%).